Behaviour of interlocking concrete slab and steel composite beam incorporated bolt shear connector - Loqman, Nadiah; Safiee, Nor Azizi; Wong, Hui Kah; Abu Bakar, Nabilah; Mohd Nasir, Noor Azline (Taylor and Francis, 2021)
The complexity of concrete and steel in composite beam has been addressed in many studies previously. However, the use of precast concrete slab in steel–concrete composite construction is considered as new, hence many factors that affect its behaviour need to be investigated. It becomes interesting when the application of interlocking tongue and groove joints between precast concrete slabs is introduced. For this purpose, a performance comparison between normal precast slab and interlocking tongue and groove precast slab in composite construction is conducted using finite element analysis. Both are designed to have full composite action using bolted shear connector. In this research, a total of five models including a control model were developed to study the flexural behaviour of designated composite beam. The model has been verified against experimental results, which showed a good agreement . Parametric studies were performed to investigate the effects of bolt size and height on flexural behaviour of the beam. The present study demonstrated that the presence of interlocking joints between slabs with larger diameter bolt can efficiently improve the stiffness of the composite system.